Citrus genetic resources in Russia, Ukraine, Belarus: conservation and management - R. V. Kulyan; L. S. Samarina; R. S. Rakhmangulov; I. V. Kikavskii; A. I. Alehna (Вавиловский журнал генетики и селекции)
Citrus genetic resources including modern and old cultivars, breeding forms and wild genotypes form the basis of the global citrus industry, that is why the preservation of the biodiversity and the creation of duplicate collections all over the world is an important task. In recent decades, there has been a sharp decline in the productivity of citrus commercial plantations in the main citrus-producing countries. The risk of an abrupt reduction in genetic diversity greatly increased because of the accumulated diseases raging there and the spread of these diseases in the neighboring citrus groves. Therefore, the preservation of biodiversity in atypical citrus regions is becoming increasingly important. The aim of this study was to compare the genetic diversity of citrus crops in the basic collections of the three countries (Russia, Ukraine and Belarus), to determine the direction and prospects for the use of available genetic resources, as well as to reveal the main problems of germplasm preservation. The comparative analysis will determine the strategy for further studies on the citrus crops in atypical areas of cultivation. The collection of citrus based in the Russian Research Institute of Floriculture and Subtropical Crops contains 132 accessions, the collection of the Belarus Botanical Garden contains 100 accessions, the collection of the Grishko National Botanical Garden contains about 60 accessions. The list of species and cultivars of three collections is presented in the article. The main problems of the successful conservation and use of citrus genetic resources are insufficient use of modern tools of germplasm characterization, the absence of a unified web-database containing all available biodiversity, the lack of consensus regarding the taxonomic position of certain genotypes. Additionally, there is a need for disease control in collections, it is necessary to develop advanced test systems for rapid diagnosis of diseases. One more important task is the extension of species diversity through the exchange of material with other foreign collections.